[LETTER REGARDING THE SMOKING ON AIRCRAFTS ISSUE] - KORNEGAY,HR (Tufts Archival Research Center, 2007)
Marginalia; Letter from the Tobacco Institute acknowledging a letter from Philip Morris Incorporated regarding smoking onboard aircraft. Expresses concern with John Banzhaf's plan to harass smokers and those supplying services to smokers.